2015
DOI: 10.1002/dev.21346
|View full text |Cite
|
Sign up to set email alerts
|

Pain‐associated stressor exposure and neuroendocrine values for premature infants in neonatal intensive care

Abstract: Recurrent stress during neonatal intensive care taxes the adaptive capacity of the premature infant and may be a risk factor for suboptimal developmental outcomes. This research used a descriptive, cross-sectional design and a life course perspective to examine the relationship between resting adrenocorticoid values at 37 postmenstrual weeks of age and cumulative pain-associated stressor exposure in prematurely born infants. Subjects were 59 infants born at under 35 completed weeks of gestation, who were at le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 57 publications
(72 reference statements)
0
7
0
Order By: Relevance
“…A recent study identified a significant negative correlation between the amount of skin-breaking procedures and the neuroendocrine marker 17-hydroxyprogesterone (17-OHP values), suggesting that exposures of recurrent pain/stressor may be a more important predicator than birthweight, gestational age, or chronological age in contributing the variance of 17-OHP levels at 37 weeks PMA. 29 In the regression analyses of our study, both weighted acute and chronic NISS scores were significantly associated with neurobehavioral outcomes, the NSTRESS and NHABIT, indicating the more painful/stressful procedures experienced in early life, the more stress signs showed and worse habituation behavior demonstrated in preterm infants. The effects of cumulative pain/stressors on neonatal neurodevelopment are still poorly studied.…”
Section: Discussionmentioning
confidence: 55%
“…A recent study identified a significant negative correlation between the amount of skin-breaking procedures and the neuroendocrine marker 17-hydroxyprogesterone (17-OHP values), suggesting that exposures of recurrent pain/stressor may be a more important predicator than birthweight, gestational age, or chronological age in contributing the variance of 17-OHP levels at 37 weeks PMA. 29 In the regression analyses of our study, both weighted acute and chronic NISS scores were significantly associated with neurobehavioral outcomes, the NSTRESS and NHABIT, indicating the more painful/stressful procedures experienced in early life, the more stress signs showed and worse habituation behavior demonstrated in preterm infants. The effects of cumulative pain/stressors on neonatal neurodevelopment are still poorly studied.…”
Section: Discussionmentioning
confidence: 55%
“…In another study, Rohan (2015) reported results of a descriptive, cross-sectional assessment of resting adrenocortical values at 37 weeks’ GA and cumulative pain-associated stressor exposure in 59 infants born at <35 completed weeks of gestation. The author identified 3,354 pain-associated procedures among the 59 infants, with an average of 56.8 per infant that had been completed by 37 weeks’ GA. Heel lance and venipuncture accounted for the majority of painful procedures.…”
Section: Resultsmentioning
confidence: 99%
“…These types of early adverse life experiences have demonstrated a negative impact on infant development. Sequelae of parent-infant separation and repeated tissue injury include epigenetic alterations that affect neurotransmitter function, can affect the hypothalamic-pituitary-adrenal axis leading to dysregulation and even decreased neuronal myelination and white matter [ [1] , [2] , [3] , [4] , [5] , [6] , [7] ]. Building on previous research, I chose to investigate how repeated painful procedures combined with alterations in serotonin expression might affect behavior and neuroanatomy.…”
Section: What Is New?mentioning
confidence: 99%